MdMYC2 and MdERF3 Positively Co-Regulate α-Farnesene Biosynthesis in Apple - Wang, Qing; Liu, Heng; Zhang, Min; Liu, Shaohua; Hao, Yujin; Zhang, Yuanhu (Frontiers in Plant Science, 2020)
a-farnesene, a sesquiterpene volatile compound plays an important role in plant defense and is known to be associated with insect attraction and with superficial scald of apple and pear fruits during cold storage. But the mechanism whereby transcription factors regulate apple a-farnesene biosynthesis has not been clarified. Here, we report that two transcription factors, MdMYC2 and MdERF3 regulated a-farnesene biosynthesis in apple fruit. Dual-luciferase assays and Y1H assays indicated that MdMYC2 and MdERF3 effectively trans-activated the MdAFS promoter. EMSAs showed that MdERF3 directly binds the DRE motif in the MdAFS promoter. Subsequently, overexpression of MdMYC2 and MdERF3 in apple calli markedly activated the transcript levels of MdHMGR2 and MdAFS. Furthermore, transient overexpression of MdMYC2 and MdERF3 in apple fruit significantly increased MdAFS expression and hence, a-farnesene production. These results indicate that MdMYC2 and MdERF3 are positive regulators of a-farnesene biosynthesis and have important value in genetic engineering of a-farnesene production.